Evaluation of the trophic level and self-cleaning ability of small flows by hydrochemical indicators (through the example of the Rpen River) - T. A. Trifonova; S. M. Chesnokova; O. V. Savelev (Юг России: экология, развитие, 2021)
Aim. Assessment by nitrification index values of the level of trophicity and toxicity for aquatic organisms in the waters of a small watercourse in an urbanized area by the content of nutrients in the water and its selfcleaning ability.Materials and Methods. The concentration of compounds of nutrients in the waters of the river was determined using the "Kapel 104T." system of capillary electrophoresis. Water was sampled for analysis according to GOST R 51592- 2000. The water content of readily oxidized organic compounds was assessed by the magnitude of permanganate oxidizability (PND F 14.1; 2.4.154-99) and difficultly oxidized compounds by the magnitude of the chemical oxygen consumption (RD 52.24.421-2012). Assessment of the water trophic level was evaluated by measuring the content of various forms of mineral nitrogen and mineral phosphorus. The aggregation index characterizing the toxicity of various forms of mineral nitrogen to aquatic organisms was calculated by their ratio to MPC for fishery reservoirs. The nitrifying ability of river waters was estimated by the value of the nitrification index (Initr.), calculated by the ratio of the concentration of nitrogen of nitrates in water to the sum of the concentrations of various forms of mineral nitrogen and the self-cleaning ability by the values of the nitrification index.Results. In terms of the aggregation index, water at all sampling points was found to be toxic. The river ecosystem is characterized by a weak ability to cleanse itself and a weak nitrifying ability, which is associated with the influence of numerous cyanotoxins on the microbiocenosis of the watercourse and filtration organisms.Conclusion. It was shown that the most sensitive indicator of trophicity of river waters is the concentration of the mineral phosphorus. Through measuring the ratio of the concentrations of mineral nitrogen to mineral phosphorus, it was established that blue-green algae (cyanobacteria), producers of cyanotoxins, dominate in the phytoplankton of the river in all the points studied.